Tinjauan Yuridis Larangan Praktik Lesbian Gay Biseksual Transgender And Queer (LGBTQ) di Indonesia Berdasarkan Pasal 28b Ayat 1 Undang-Undang Dasar 1945 - Irvan, Irvan; Hariansah, Syafri; Tribuana, Robi Rendra (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
The prohibition of LGBTQ practices in Indonesia based on article 28B paragraph 1 of the 1945 Constitution is a controversial issue. The article reads,